2022
DOI: 10.1109/tem.2020.3001764
|View full text |Cite
|
Sign up to set email alerts
|

Crowdfunding for Design Innovation: Prediction Model With Critical Factors

Abstract: Online reward-based crowdfunding campaigns have emerged as an innovative approach for validating demands, discovering early adopters, and seeking learning and feedback in the design processes of innovative products. However, crowdfunding campaigns for innovative products are faced with a high degree of uncertainty and suffer meager rates of success to fulfill their values for design. To guide designers and innovators for crowdfunding campaigns, this paper presents a data-driven methodology to build a predictio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The developed business model utilizes the Business Model Canvas, and the proposed crowdfunding business model is specifically designed for non-profit organizations [33]. Further research on crowdfunding has also been conducted by Chaoyang Song, Jianxi Luo, Katja Hölttä-Otto, Warren Seering, and Kevin Otto [34]. Using the Data-driven and Critical Factors methods, this study construct a prediction model with important factors for success of reward-based CFP.…”
Section: Governance Of Cfp and Oimentioning
confidence: 99%
“…The developed business model utilizes the Business Model Canvas, and the proposed crowdfunding business model is specifically designed for non-profit organizations [33]. Further research on crowdfunding has also been conducted by Chaoyang Song, Jianxi Luo, Katja Hölttä-Otto, Warren Seering, and Kevin Otto [34]. Using the Data-driven and Critical Factors methods, this study construct a prediction model with important factors for success of reward-based CFP.…”
Section: Governance Of Cfp and Oimentioning
confidence: 99%
“…The impact of digital financial inclusion development on enterprises is more about improving the efficiency of financing and improving the level of financial stability. [ 32 ] Internet finance can help enterprises obtain a more comprehensive range of financial support, improve their financing efficiency and reduce their financing costs, and [ 33 ] argue that new technologies can help match the supply and demand of funds over long distances and improve the efficiency of capital use. The development of information technology also helps overcome the information asymmetry problem in traditional financial markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The crowdsourced solutions make it possible to mine the real-world ideation outputs of complex cognitive tasks generated by thousands of people across the world. In addition, some researchers have observed that crowdfunding platforms (e.g., Kickstarter and Indiegogo) also accumulate product design projects and contain rich design information about product designs, and are therefore potentially useful data sources for analogical design stimuli [100].…”
Section: Patentsmentioning
confidence: 99%
“…Both have been used in many data-driven DbA studies [5,15,64]. Although crowdsourced design data [97,98,99] and crowdfunded project data [100] have been explored in design research and are also potentially useful for DbA studies, they have not been fully exploited. In addition, most of the current data-driven DbA methods were designed to merely mine textual information as analogy candidates; only a few researchers have focused on the data of other modalities [13,92].…”
Section: Future Opportunities and Directionsmentioning
confidence: 99%